Tune In, Log On : Soaps, Fandom, and Online Community. - Baym, Nancy K. (New media cultures., 1999)
Tune In, Log Out is an ethnographic study of an Internet soap opera fan group. Bridging the fields of computer-mediated communication and audience studies, the book shows how verbal and non verbal communicative practices create collaborative interpretations and criticism, group humor, interpersonal relationships, group norms and individual identity. While much has been written about problems and inequities women have encountered online, Nancy K Baym's analysis of a female-dominated group in which female communication styles prevail demonstrates that women can build successful online communities while still welcoming male participation. In addition, a longitudinal look at the development of fan group allows an examination of the endurance of the group's social structure in the face of the Internet's tremendous growth. Lively and engaging, Tune In, Log Out provides an entertaining introduction to issues of online and audience community.